2004
DOI: 10.1088/1126-6708/2004/02/015
|View full text |Cite
|
Sign up to set email alerts
|

Analytic non-supersymmtric background dual of a confining gauge theory and the corresponding plane wave theory of Hadrons

Abstract: We find a regular analytic 1st order deformation of the Klebanov-Strassler background. From the dual gauge theory point of view the deformation describes supersymmetry soft breaking gaugino mass terms. We calculate the difference in vacuum energies between the supersymmetric and the non-supersymmetric solutions and find that it matches the field theory prediction. We also discuss the breaking of the U (1) R symmetry and the space-time dependence of the gaugino bilinears two point function. Finally, we determin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
125
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(133 citation statements)
references
References 39 publications
6
125
0
2
Order By: Relevance
“…Since the solution was not glued to the UV Klebanov-Strassler asymptotic solution, two integration constants for the flux functions, called b f and b k , were not fixed. In principle these two parameters are not independent and the precise relation between them could be determined in the UV by gluing to the KS solution or to one of its non-normalizable deformations [38,39]. However, as we will see below, the physics is completely independent of the details of the UV.…”
Section: The Ns5 Polarization Potential and The Tachyonmentioning
confidence: 99%
“…Since the solution was not glued to the UV Klebanov-Strassler asymptotic solution, two integration constants for the flux functions, called b f and b k , were not fixed. In principle these two parameters are not independent and the precise relation between them could be determined in the UV by gluing to the KS solution or to one of its non-normalizable deformations [38,39]. However, as we will see below, the physics is completely independent of the details of the UV.…”
Section: The Ns5 Polarization Potential and The Tachyonmentioning
confidence: 99%
“…In order to break supersymmetry we will consider an effective 5D model that is motivated from a 10D type IIB supergravity solution [19], obtained by perturbing the well-known Klebanov-Strassler supersymmetric background [16], using techniques developed in [18]. In Appendix D, we describe in detail how the effective deformed nonsupersymmetric 5D background metric is obtained from a dimensional reduction of the 10D metric.…”
Section: A Deformed Adsmentioning
confidence: 99%
“…In fact there exist deformations of the Klebanov-Strassler background that softly break all of the supersymmetry in the infrared (IR) of the 4D theory [18,19]. It will be shown that when the ten-dimensional (10D) supergravity theory is reduced to five dimensions, the background geometry is a deformation of AdS 5 , with the modification growing stronger as one moves further into the AdS throat-corresponding to SUSY-breaking near the "IR brane" of phenomenological models.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations